Comparison of sonographic lung comet evaluation by an experienced ultrasonographer and novice in a high-altitude environment - Vogts, Ferdinand Wilhelm (Department of Human Biology, 2023)
Introduction: High altitude illness can be severely debilitating and sometimes fatal to those visiting higher altitudes. The condition is known to develop at altitudes above 2500m and has an incidence of between 50 and 60 percent. High altitude pulmonary oedema (HAPE) presents with signs and symptoms related to the accumulation of extravascular fluid in the lung, and early identification is critical to timeous intervention which in turn improves clinical outcomes. While increases in altitude result in physiological acclimatization, being able to identify when these changes become pathological is vital to early intervention. This process is facilitated with the use of lung ultrasound and the identification of sonographic artifacts called lung comets. This study was designed to establish whether a novice sonographer can perform effective assessment of lung ultrasound comet scores in comparison to an experienced sonographer in a high-altitude environment. An acceptable limit of agreement of 4 lung comets were identified a priori. This value was established based on the work done by Volpicelli et al. in 2006 who defined a positive lung ultrasound test as having at least 3 lung comets present at the time of examination.[49] In addition, various physiological and clinical parameters and their changes at different altitudes, ranging from 950 to 4662 meters above sea level, were assessed to aid the clinical interpretation and relevance of the ultrasound findings. Methods: Ten participants (six male; four female) underwent daily lung ultrasound scans at varying altitudes on Mount Kilimanjaro according to a standardized 8-zone protocol. One experienced sonographer scanned each participant, with his score then used as the “gold standard” for comparison, followed by a novice sonographer. The two sonographers were blinded to each other's findings during the data collection. Participants also undertook daily Lake Louise Scores, fingertip peripheral oxygen saturation readings and heart rates as part of the safety and clinical monitoring program on the mountain. Results: An exploratory Bland-Altman analysis revealed that compared to experts, novices showed little bias in identifying lung comets with sonography (mean difference 0,2 comets, 95% CI -0,2 to 0,6). Novice total comet scores typically fell within a range of approximately 3 above and below the expert score. There was a statistically significant difference in the total number of lung comets across the 7 recorded altitude points, χ2 (6) = 22.05, p < 0.01, as measured by the expert ultra sonographer. In addition, there was an overall statistically significant difference across the 7 recorded altitude points with regards to oxygen saturation (χ2 (6) = 33.22, p < 0.001), heart rate (as a percentage of maximum heart rate) (χ2 (6) = 12.83, p < 0.05) and Lake Louise Scores (χ2 (6) = 30.59, p < 0.001). Conclusion: Our results suggest that a novice sonographer is able to perform an effective assessment of lung ultrasound comet scores when compared to an experienced sonographer in a high-altitude environment. While the limited sample size of this study advocates for corroboration with future research projects on a larger scale, our preliminary findings encourage the use of a portable ultrasound machine as a potentially useful diagnostic tool in a wilderness expedition kit. The significant effects of high-altitude on physiological parameters are again emphasized, with our results in keeping with the findings of previous authors.